(untitled) - Mariotti, Steve (Boston, 2015)
Written by award-winning experts, Steve Mariotti and Caroline Glackin, Entrepreneurship and Small Business Management presents complex economic, financial and business concepts in a manner easily understood by a variety of students.
Keywords: Doanh nghiệp nhỏ,Small business; Quản lý,Management